An atypical case of atypical pneumonia. (3rd June 2018) - Ota, Koshi; Iida, Ryo; Ota, Kanna; Sakaue, Masahide; Taniguchi, Kohei; Tomioka, Masao; Nitta, Masahiko; Takasu, Akira
Abstract: Atypical pneumonia has been thought to account for 7%‐20% of community‐acquired pneumonia (CAP). The treatment for the pathogens that cause atypical pneumonia is different from that of other bacterial pneumonia. Therefore, identification of the causative pathogen in a primary care situation is crucial for adequate treatment of CAP. Mycoplasma infection is prevalent in the general population, but Mycoplasma pneumoniae with extrapulmonary symptoms is relatively rare. Herein, we report a case of CAP because of M. pneumoniae that presented with a wide variety of extrapulmonary diseases. Delayed administration of appropriate antibiotics may contribute to development of extrapulmonary manifestations. Abstract : We report a case of community‐acquired pneumonia due to M. pneumoniae that presented with a wide variety of extrapulmonary diseases. Delayed administration of appropriate antibiotics may contribute to development of extrapulmonary manifestations.